2018
DOI: 10.1021/acsmacrolett.8b00594
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Polymer Polarity on Ion Transport: A Competition between Ion Aggregation and Polymer Segmental Dynamics

Abstract: In this work, we use computer simulations to demonstrate that there may be limits to which polymer polarity alone can be used to influence the ionic conductivity of salt-doped polymer electrolytes. Specifically, we use coarse-grained molecular dynamics simulations to probe the effect of the polarity of the polymer electrolyte upon ion mobilities and conductivities of dissolved salts. At low polymer polarities, increasing the polymer dielectric constant reduces ionic aggregation and the resultant correlated ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

23
184
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 91 publications
(209 citation statements)
references
References 53 publications
(79 reference statements)
23
184
1
Order By: Relevance
“…Interestingly, the conductivity did not scale monotonically with the T g of the polymers suggesting additional contributions playing a major role in the ion mobility. Follow-up studies reported by Wheatle et al 29,30 confirmed the relevance of the polymer backbone polarity by comparing computational and experimental results obtained for different structures 29 and by claiming the existence of an optimal compromise between ion solvation and segmental mobility that must be taken into account in designing novel PEs. 30 Using different heteroatoms than oxygen in the polymer structure is a straightforward method to modify both chain mobility and polarity.…”
Section: Introductionmentioning
confidence: 69%
See 4 more Smart Citations
“…Interestingly, the conductivity did not scale monotonically with the T g of the polymers suggesting additional contributions playing a major role in the ion mobility. Follow-up studies reported by Wheatle et al 29,30 confirmed the relevance of the polymer backbone polarity by comparing computational and experimental results obtained for different structures 29 and by claiming the existence of an optimal compromise between ion solvation and segmental mobility that must be taken into account in designing novel PEs. 30 Using different heteroatoms than oxygen in the polymer structure is a straightforward method to modify both chain mobility and polarity.…”
Section: Introductionmentioning
confidence: 69%
“…Follow-up studies reported by Wheatle et al 29,30 confirmed the relevance of the polymer backbone polarity by comparing computational and experimental results obtained for different structures 29 and by claiming the existence of an optimal compromise between ion solvation and segmental mobility that must be taken into account in designing novel PEs. 30 Using different heteroatoms than oxygen in the polymer structure is a straightforward method to modify both chain mobility and polarity. Specifically, the presence of sulfur heteroatoms in combination with oxygen has been proved to give encouraging results for lithium transport, even though crystallinity is not prevented.…”
Section: Introductionmentioning
confidence: 69%
See 3 more Smart Citations